Developmental Transcriptomics Reveals a Gene Network Driving Mimetic Color Variation in a Bumble Bee. (21st April 2021) - Rahman, Sarthok Rasique; Terranova, Tatiana; Tian, Li; Hines, Heather M
Abstract: A major goal of evolutionary genetics and evo-devo is to understand how changes in genotype manifest as changes in phenotype. Bumble bees display remarkable color pattern diversity while converging onto numerous regional Müllerian mimicry patterns, thus enabling exploration of the genetic mechanisms underlying convergent phenotypic evolution. In western North America, multiple bumble bee species converge onto local mimicry patterns through parallel shifts of midabdominal segments from red to black. It was previously demonstrated that a Hox gene, Abd-B, is the key regulator of the phenotypic switch in one of these species, Bombus melanopygus, however, the mechanism by which Abd-B regulates color differentiation remains unclear. Using tissue/stage-specific transcriptomic analysis followed by qRT–PCR validation, this study reveals a suite of genes potentially involved downstream of Abd-B during color pattern differentiation. The data support differential genes expression of not only the first switch gene Abd-B, but also an intermediate developmental gene nubbin, and a whole suite of downstream melanin and redox genes that together reinforce the observed eumelanin (black)-pheomelanin (red) ratios. These include potential genes involved in the production of insect pheomelanins, a pigment until recently not thought to occur in insects and thus lacking known regulatory enzymes. The results enhance understanding of pigmentation gene networks involved in bumble bee color pattern development and diversification, while providing insights into how upstream regulators such as Hox genes interact with downstream morphogenic players to facilitate this adaptive phenotypic radiation.